Oral food desensitization in children with IgE‐mediated hen's egg allergy: a new protocol with raw hen's egg. Issue 1 (13th August 2012) - Meglio, Paolo; Giampietro, Paolo G.; Carello, Rossella; Gabriele, Ida; Avitabile, Simona; Galli, Elena
<x xml:space="preserve">Abstract</x> To cite this article: Meglio P, Giampietro PG, Carello R, Gabriele I, Avitabile S, Galli E. Oral food desensitization in children with IgE‐mediated hen's egg allergy: a new protocol with raw hen's egg. Pediatr Allergy Immunol 2012: 00. Abstract Background: Hen's egg allergy affects young children and can cause severe allergic reactions. Avoidance results in dietary limitations and can affect the quality of life, especially in cases where potentially life‐threatening reactions exist. Our objective was to desensitize children with moderate‐severe IgE‐mediated hen's egg allergy over a 6‐month period, by introducing increasing and very gradual daily doses of raw hen's egg in order to enable the children to assume 25ml of this food, or to induce tolerance to the highest possible dose. The protocol foresaw the egg reintroduction in the home setting. Methods: In this randomized, controlled open study, 20 hen's egg allergic children (10 in the active group) were admitted. A convincing history or a positive double‐blind placebo‐controlled food challenge confirmed the diagnosis. Oral desensitization was performed with increasing doses starting from 0.27 mg of hen's egg proteins (1 drop of raw hen's egg diluted 1:100). We adopted an original, mathematically calculated protocol in order to ensure a constant, daily increment of doses. Results: 8/10 children (80%) in the active group achieved the daily intake of 25ml over a 6‐month period. One child (10%) could tolerate up to 2ml/day while another child (10%) failed the desensitization. Six months after enrolment only 2 children in the control group (20%) could tolerate hen's egg. Conclusions: We successfully desensitized 8/10 children with IgE‐mediated hen's egg allergy in a 6‐month period. The partial outcome in the child who could tolerate 2ml/day reduced the risk of severe reactions after unnoticed introduction of egg. A regular protocol that ensures a daily constant increase of doses helps to reduce possible adverse events, thus improving safety and effectiveness.